Self-Super Parasitism Behavior of Naive and Experienced Cotesia Vestalis, A Bio-Control Agent of Plutella Xylostella in Brassica Crops - Khumairoh, Uma; Pandjaitan, Catlyn (AGRIVITA, Journal of Agricultural Science, 2011)
Cotesia vestalis is one of the parasitoids of Plutella xylostella,. They do self-superparasitism to predicted as a behavior to increase the proportion of their female offspring or as a behavior resulting from their inability to recognize previously parasitized hosts. Observations were conducted to study the behavior of experienced and naive Cotesia vestalis. The age of C. vestalis females for observation was between one to three days after emerging for both experienced and naïve, but experienced C. vestalis were trained to lay eggs before real observation. The observation was done in a laboratory and included five behaviors, namely number of ovipositions and host encounters, period of grooming, walking and resting. There was no significant difference in the proportion experienced and naïve C. vestalis females that superparasitized. The number of ovipositions and host encounters, periods of walking, grooming and resting were also not significantly different between experienced and naïve C. vestalis. For further research, it is recommended to observe behavior of C. vestalis that differ in age and after longer periods of experience training. Additional behavior such as direction preferences (leaf or patches), host preference (host health and color) can additionally be important variables to study in C.vestalis behavior. Keywords: Superparasitism, C. vestalis, naive, experienced, behavior